Optimalisasi Self Care pada Penderita Hipertensi melalui Edukasi Latihan Relaksasi Otot Progresif - Wa Ode Sri Asnaniar; Nur Wahyuni Munir; Akbar Asfar; Safruddin; Wan Sulastri Emin; Samsualam; Yutia Ferianti Yunus Padu; Nur Intan Ana Sofyan; Jabal Nur Djafar (Sagamedia Indo Press, 2023)
Hypertension is one of the causes of premature death because it is associated with the risk of cardiovascular disease. Management of hypertensive patients can be in the form of self care management carried out by hypertensive patients. One of the non-pharmacological therapies that can be done independently by people with hypertension is progressive muscle relaxation. This community service activity aims to improve self-care for people with hypertension through progressive muscle relaxation training education. The methods of devotion are lectures, demonstrations, and using Leaflet media. From carrying out community service activities in the form of education to increase self-care management of hypertension by doing progressive muscle relaxation exercises, the knowledge and skills of the community are obtained after the provision of education increases. People become relaxed and comfortable after doing progressive muscle relaxation. Progressive muscle relaxation can be done independently anywhere and anytime by people with hypertension.